From Between the trace and the index: Contemporary Readings of André Bazin - Esqueda Verano, Lourdes; Cuevas Álvarez, Efrén (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2012)
As a consequence of the turn from analogic to digital media, the debate around the notion of “realist media” has acquired a newfound importance. This debate has been articulated quite often coming from the classic authors of the realist theory, within which Andre Bazin occupies a prominent position. This article analyzes some of these contemporary new readings of Bazin’s thought, namely, those of Stanley Cavell, Dudley Andrew, Philip Rosen, Daniel Morgan and Lee Carruthers. All these renew the principal tenets of the French critic’s theory, from the ontology of the medium to his novel understanding of the temporal dimension, linked to concepts such as ambiguity or realism. The article closes with some remarks on the actuality of Bazin’s thought in relation to the new digital paradigm.